Bioinspired scaffolds that sequester lead ions in physically damaged high efficiency perovskite solar cells. Issue 8 (5th January 2021) - Mokhtar, Muhamad Z.; He, Jiangyu; Li, Menghan; Chen, Qian; Ke, Jack Chun Ren; Lewis, David J.; Thomas, Andrew G.; Spencer, Ben F.; Haque, Saif A.; Saunders, Brian R.
Abstract : When hydroxyapatite nanoparticles are included in the mesoporous scaffold for perovskite solar cells they not only improve the power conversion efficiency but sequester released Pb if broken cells are immersed in water. Abstract : Hydroxyapatite nanoparticles (HAP NPs) are blended with TiO2 NPs to prepare mixed mesoporous scaffolds which are used to prepare high efficiency perovskite solar cells (PSCs) with a best power conversion efficiency (PCE) of 20.98%. HAP not only increases the PCE but also limits the concentration of Pb released in water from intentionally broken PSCs by ion sequestration thereby potentially offering a promising in-device fail-safe system.